Long-term explant culture: an improved method for consistently harvesting homogeneous populations of keloid fibroblasts. Issue 1 (1st January 2022) - Li, Jing; Zou, Yuqing; Wang, Song; Guo, Shikai; Huang, Zhishun; Huo, Ran
ABSTRACT: Explant culture is a more suitable method than enzyme digestion for the isolation of keloid fibroblasts (KFs), but it has a longer isolation period. In this study, we propose a long-term explant culture method. Unlike in the conventional explant culture method, we continued culturing explants to isolate KFs rather than discarding them during passage. We demonstrated that keloid explants could be cultured for more than 4 months to continuously yield enriched KFs, and the KFs from the repeatedly cultured explants had shorter isolation times. The biological behavior and fibrotic phenotypic characteristics of the KFs from the explants cultured long term were investigated, and no statistical differences were found compared with the KFs from the original explants. In conclusion, the long-term explant culture method was shown to be efficient for harvesting a large, homogeneous population of KFs. The high efficiency as well as ease of operation and sample saving make this method convenient for researchers working with KFs.